Influence of Tree-Crop Distance on Growth of Pinus patula and Cupressus lusitanica in Plantation Establishment and Livelihood Improvement Scheme - Ingura, Isaac Omoding; Kirongo, Balozi Bekuta; Odhiambo, Kenneth Opiyo (European Journal of Applied Sciences, 2024)
The Plantation Establishment and Livelihood Improvement Scheme (PELIS), is an approach of raising young seedlings in a plantation whereby communities are given small areas of forest land with seedlings to till and take care of the planted seedlings until they reach canopy closure. But the system has had a number of managerial issues, the most prominent being that there is no recommended distance between the seedlings and crops (tree-crop distance). Thus, farmers plant their food crops immediately next to the young tree seedlings thus exacerbating intra-specific competition. Some of the crops planted include maize, cabbages and Irish potatoes. These crops cause excessive competition for moisture, nutrients, space and light to the detriment of the desired tree seedlings. The result has been massive failures of young plantations, while those that are cited as “successful” end up with poor growth rates and poor form not suited for the objectives of plantation establishment. This study was set up to elucidate the effects of tree-crop distance on the growth of Pinus patula and Cypress lusitanica seedlings in a PELIS system so as to come up with an optimum distance for tree-crop in a PELIS system of establishment. The treatments constituted plantation tree species (P. patula and C. lusitanica) and crops (cabbages and potatoes) at tree-crop distances of 20cm, 50cm, 100cm and 150cm. The control for the experiment was at tree-crop distance of 20cm. Plots of 5 × 5 tree seedlings with a weed free zone at the center (3x3 seedlings) were set up for C. lusitanica and P. patula. The inner 3 × 3 tree seedlings were assessed monthly for height and root collar diameter growth from time of transplanting while the outer trees formed the guard row. The experiment was in Complete Randomized Block Design (CRBD) in 2 replicates. The study was in two sites, Timboroa and Kipkurere. ANOVA analyses were performed on the data (P < 0.05) and significant treatments were discriminated using Turkey’s HSD test. The results showed that the best growth in RCD and height occurred at tree-crop distance of 100 cm which was significantly higher than the control (P < 0.05) at both sites. The research demonstrated that in PELIS tree-crop distance is an important factor that affects the growth of tree seedlings and therefore we recommend tree-crop distance of 100 cm for successful C. lusitanica and Pinus patula establishment.